Exploring the Association Between Hyperprolactinemia and Infertility in Women: Insights From a Study of 170 Patients - Shabnam, Shahida Karamat, Rubina Amjad, Yaman Shahid, Zarina Khan, Nazneen Iqbal (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Hyperprolactinemia is a common endocrine disorder in women that is closely associated with infertility. Elevated prolactin levels can disrupt reproductive functions, particularly ovulation, and menstrual cycles, leading to challenges in conception. This study aims to examine the association between hyperprolactinemia and infertility in women, analyzing the clinical characteristics, causes, and treatment outcomes of 170 patients. Methods: A retrospective study was conducted involving 170 women diagnosed with hyperprolactinemia and infertility. Clinical data, including prolactin levels, menstrual history, causes of hyperprolactinemia, and treatment outcomes, were collected. Dopamine agonists such as bromocriptine and cabergoline were the main treatment options. The effects of treatment on prolactin levels and subsequent fertility outcomes were analyzed. Results: The majority of the patients presented with irregular menstrual cycles (65%) and anovulation (55%). Prolactinomas were the leading cause of hyperprolactinemia (40%), followed by medication-induced hyperprolactinemia (25%) and hypothyroidism (20%). Following treatment with dopamine agonists, 72% of patients experienced normalization of prolactin levels, and 55% achieved successful conception. Conclusion: Hyperprolactinemia is a significant cause of infertility in women, with dopamine agonists proving effective in restoring normal prolactin levels and improving fertility outcomes. Early diagnosis and appropriate treatment are essential for improving reproductive health. Keywords: Hyperprolactinemia, Infertility, Dopamine agonists, Prolactin, Anovulation, Prolactinoma, Menstrual irregularities, Fertility